Poverty Policy: Between Hope and Reality - Yusriadi, Yusriadi; Kurniawaty; Sibali, Alwi; Mattalatta (Journal of Indonesian Scholars for Social Research, 2023)
This study examines the inherent duality in poverty policy, analyzing the discrepancy between the goals established by policies and the actual outcomes of their execution. The study employs an analytical methodology to examine diverse poverty programs implemented in various countries, emphasizing their accomplishments and shortcomings. The paper begins by providing an overview of the historical development of poverty policy and elucidating how economic and social perspectives have influenced strategies for poverty management. The study subsequently explores the implementation of these rules, encompassing the frequently encountered issues and obstacles. Emphasis is placed on examining case studies that demonstrate effective poverty reduction measures and cases when expectations were not fulfilled. Using data and case studies, the paper examines the crucial aspects that impact the efficacy of poverty initiatives, including the political framework, economic resources, and community participation. In addition, the topic encompasses the influence of technology and innovation on developing more flexible and receptive poverty policies. Ultimately, the study thoroughly examines the interplay between theory and practice in poverty policy. This indicates that a more all-encompassing and inclusive strategy may be required to tackle poverty concerns effectively. Hence, the article's objective is to offer valuable perspectives for policymakers, practitioners, and academics concerned with addressing poverty in a constantly evolving global environment.